Thermodynamic performance and water consumption of hybrid cooling system configurations for concentrated solar power plants - Asfand, Faisal; Palenzuela, Patricia; Roca, Lidia; Caron, Adèle; Lemarié, Charles-André; Gillard, Jon; Turner, Peter J.; Patchigolla, Kumar (MDPI, 2020)
The use of wet cooling in Concentrated Solar Power (CSP) plants tends to be an unfavourable option in regions where water is scarce due to the high water requirements of the method. Dry-cooling systems allow a water consumption reduction of up to 80% but at the expense of lower electricity production. A hybrid cooling system (the combination of dry and wet cooling) offers the advantages of each process in terms of lower water consumption and higher electricity production. A model of a CSP plant which integrates a hybrid cooling system has been implemented in Thermoflex software. The water consumption and the net power generation have been evaluated for different configurations of the hybrid cooling system: series, parallel, series-parallel and parallel-series. It was found that the most favourable configuration in terms of water saving was series-parallel, in which a water reduction of up to 50% is possible compared to the only-wet cooling option, whereas an increase of 2.5% in the power generation is possible compared to the only-dry cooling option. The parallel configuration was the best in terms of power generation with an increase of 3.2% when compared with the only-dry cooling option, and a reduction of 30% water consumption compared to the only-wet cooling option
Keywords: water consumption; power block; concentrated solar power; hybrid cooling systems